A Comparison of Profile, Race and FKG Systems in Eliminating Enterococcus Faecalis from the Apical Third of Mandibular Premolars - K. Nazari Moghaddam; P. Owlia; A. Baghalian (Tehran University of Medical Sciences, 2006)
Statement of problem: Microorganisms are essential for the development of periradicular diseases and are one of the major causative factors associated with endodontic treatment failures. Different instruments and preparation techniques have been developed in Endodontics to eliminate or reduce intracanal bacteria. Purpose: The aim of this study was to compare the amount of remaining E. faecalis in the apical third of root canals following instrumentation with Profile, Race and FKG files. Materials and Methods: Ninety freshly extracted mandibular single canal premolars were selected. A horizontal groove was made circumferentially around the roots at a depth of 0.5 mm and a distance of 5 mm from the anatomic apex. All the equipments were sterilized overnight by ethylene oxide gas. Root canals, inoculated with E. faecalis suspension, were prepared using Profile, Race or FKG instruments in a step-back technique. Master apical file, amount of irrigant for each canal and working length were similar in all specimens groups. Following preparation, the apical portions of the roots were separated from the previously made grooves and were sampled by sterile paper points. Statistical analysis was performed using ANOVA and Duncan's multiple range tests. Results: Profile was significantly more effective in eliminating E. faecalis as compared to Race. A significant difference was not observed between FKG and the other two studied instrumentation techniques. Conclusions: Neither of the methods could completely eliminate E. faecalis from the root canals.